Analyzing the Impact of Smartphone Use and Mobile Distraction in Higher Education - Khatiwada, Shreeraj (International Research Journal of MMC (IRJMMC), 2025)
This study explores the impact of smartphone use and mobile distraction on the academic performance of college students. Utilizing a mixed-methods approach, data were collected from 286 students through surveys and open-ended responses. Quantitative analysis revealed that a majority of students use smartphones for 4–6 hours daily, with social media, entertainment, and messaging as primary activities. Chi-squared tests showed significant associations between academic performance and factors such as usage duration, frequency of checking phones while studying, anxiety over disconnection, perceived addiction, procrastination, and impact on sleep and mental health. Sentiment analysis indicated that while many students acknowledge the academic benefits of smartphones, a substantial portion reported negative effects like distraction and stress. Thematic analysis of student suggestions highlighted the importance of self-regulation, time management, and institutional support. The findings underscore the need for targeted digital wellness initiatives to mitigate mobile distraction and enhance academic success.